2022
DOI: 10.3390/su14106376
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Partnerships in Japanese Firms’ Logistics Outsourcing: From a Sustainable Perspective

Abstract: This study aimed to reveal the actual state of Japanese firms’ logistics outsourcing, and examine their relationship with LSPs. This study addressed the following issues by conducting a case study of six leading manufacturing firms. First, it clarified the characteristics of Japanese-style logistics outsourcing as: the outsourcing of the total activities, the consigning to a single LSP, and the development of advanced information systems. Moreover, it examined the logistics outsourcing performance from a susta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…, 2021), long-term R&D planning (Young et al. , 2020), long-term partnerships (Shi et al. , 2022) and long-term corporate social responsibility (Yan et al.…”
Section: Cross-case Analysis and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, 2021), long-term R&D planning (Young et al. , 2020), long-term partnerships (Shi et al. , 2022) and long-term corporate social responsibility (Yan et al.…”
Section: Cross-case Analysis and Discussionmentioning
confidence: 99%
“…For supply chain lifecycle, we focus on the long-term planning for SSCT. According to the literature review, considering issues from a long-term planning perspective plays a crucial role in achieving long-term prosperity of the supply chain, such as long-term capacity planning (Smirnov et al, 2021), long-term R&D planning (Young et al, 2020), long-term partnerships (Shi et al, 2022) and long-term corporate social responsibility (Yan et al, 2023). Florez-Jimenez et al (2024) pointed out that corporate sustainability is one of the three necessary factors for achieving long-term survival of enterprises.…”
Section: Strategy For Ssctmentioning
confidence: 99%
“…Logistics outsourcing is a base for developing strong business relationships [26] because the LSPs help strengthen their clients' core business. To deliver the benefits of logistics outsourcing, LSPs should develop relationships based on trust and cooperation with their clients to achieve high service quality and effective returns management and reverse logistics [34]. Strong relationships are dependent on the amount, speed, and quality of information shared between the LSPs and their clients; as such, the information shared should improve planning and problem sharing to build sustainable business relationships.…”
Section: Relationship Managementmentioning
confidence: 99%
“…Better performance outputs, such as increased competitiveness and reduced transaction costs, may be achieved in buyer-supplier partnerships when there is trust between purchasers and sellers in the retail business (see Table 1). Authors in [14] concluded that trust had the greatest influence on getting cooperation in relationships, but Shi, Park, Sugie, and Fukuzawa [15] revealed that trust influences long-term partnerships. Orsini et al [16] demonstrate the value of trust in preserving established channel connections.…”
Section: Trustmentioning
confidence: 99%